Miniaturized Arrow-Shaped Flexible Filter-Embedded Antenna for Industrial and Medical Applications - Musa Hussain; Anees Abbas; Wahaj Abbas Awan; Syeda Iffat Naqvi (Applied Sciences)
This paper presents the design and characterization of a coplanar waveguide (CPW) fed, low-profile, and flexible arrow-shaped filtenna for ISM band applications at 2.45 GHz. The antenna design involves an innovative approach incorporating etching slots to achieve miniaturization by 34%, contrasting with a traditional quadrilateral-shaped antenna. After the attainment of desired miniaturization, the unwanted harmonics are also mitigated by deploying simple filtering methodology. A perpendicular rectangular stub is strategically introduced to the feedline, effectively minimizing harmonics across a broad frequency range of 3.3–11.0 GHz. Through simulations and measurements, the results indicate that the antenna’s operational band spans from 2.276 to 2.75 GHz, encompassing the entire ISM band (2.4–2.5 GHz). Notably, the antenna demonstrates promising radiation characteristics, including omnidirectional gain of approximately 2.2 dBi and a radiation efficiency exceeding 95%. With a compact overall size of 0.24λ × 0.20λ × 0.0005λ (where λ is the free-space wavelength at 2.45 GHz), coupled with wide harmonic rejection property, the proposed arrow-shaped flitenna emerges as a compelling candidate for ISM band applications.